Clinicopathological and Genetic Features in Superficial Nonampullary Duodenal Epithelial Tumors - Atsushi Sawada; Kingo Hirasawa; Makoto Sugimori; Yuichiro Ozeki; Ryosuke Ikeda; Masafumi Nishio; Takehide Fukuchi; Ryosuke Kobayashi; Hiroaki Kaneko; Chiko Sato; Yoshiaki Inayama; Chikara Kunisaki; et al. (Gastroenterology Research and Practice)
Conclusions:GNAS mutations are more common in gastric-type SNADETs than in the intestinal type. As GNAS mutations are continuously present from adenoma to adenocarcinoma, resection at the adenoma stage is desirable.